2021
DOI: 10.3390/s21206831
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Sensor-Based Prediction Model of Timed up and Go Test in Older Adults

Abstract: The Timed Up and Go (TUG) test has been frequently used to assess the risk of falls in older adults because it is an easy, fast, and simple method of examining functional mobility and balance without special equipment. The purpose of this study is to develop a model that predicts the TUG test using three-dimensional acceleration data collected from wearable sensors during normal walking. We recruited 37 older adults for an outdoor walking task, and seven inertial measurement unit (IMU)-based sensors were attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…For the step event detection and feature extraction methods, the same methods as in our previous works were used [ 24 , 25 ]. We used a peak detection method for the step detection by recognizing the highest peak of vertical acceleration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the step event detection and feature extraction methods, the same methods as in our previous works were used [ 24 , 25 ]. We used a peak detection method for the step detection by recognizing the highest peak of vertical acceleration.…”
Section: Methodsmentioning
confidence: 99%
“…A total 60 features were normalized by centering data and then used for this study. Detailed methods for the step detection and feature extraction are well described in [ 24 , 25 ], respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We extracted features that have demonstrated to be useful in mobility studies [ 36 , 37 ]. First, 20 base features were extracted, of which the descriptions and formulas are presented in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This was repeated 12 times using the leave-one-subject-out as the test set protocol. Gait studies on mobility have demonstrated that good prediction metrics can be achieved with only eight to 10 features while balancing model complexity and computational cost [ 35 , 37 ]. Hence, we selected only the top 10 features at each iteration.…”
Section: Methodsmentioning
confidence: 99%
“…A step event was recognized by detecting heel-strike using the peak detection algorithm with data obtained by accelerometers [22], [23].…”
Section: Data Processing 1) Step Time Variabilitymentioning
confidence: 99%